Analysis of damage characteristics of reinforced concrete slabs under explosive impact and research on CFRP reinforcement - Lian, Junxia; Li, Dongjie; Zhao, Haonan (Frontiers in Materials, 2024)
To study the damage characteristics and damage model of reinforced concrete slabs under explosive impact, the failure modes of reinforced concrete slabs under near-field and contact explosion were first studied through on-site experiments. A coupled model was established based on the Coupled Eulerian-Lagrangian (CEL) method using AUTODYN finite element software. The reliability of the model was verified by comparing the numerical simulation results with experimental results. Based on this, a fully coupled model of Carbon Fiber Reinforced Polymer (CFRP) reinforcement for reinforced concrete slabs under contact explosion was established, and the influence of different CFRP thicknesses and reinforcement methods on the blast resistance performance of reinforced concrete slabs was discussed. The research results indicate that under the action of near-field explosions, the front face of reinforced concrete slabs mainly experiences slight peeling damage, and the central area of the back face forms seismic collapse and peeling damage, with damage cracks diverging from the center to the surrounding areas; Under the action of contact explosion, the front face of the reinforced concrete slab produces blast pits, the back face forms a seismic collapse zone, and peeling damage occurs; The CFRP reinforcement layer can improve the blast resistance performance of reinforced concrete slabs; There is an optimal thickness when using CFRP to enhance the blast resistance of reinforced concrete slabs.